Nutrition status among Children under 5 years in Ibalikoma Village Apac District. A Cross-sectional Study. - Odot , Rebecca (Student’s Journal of Health Research Africa, 2022)
Abstract The study was conducted in Ibalikoma Village Apac District to assess the factors influencing the nutritional status of children under 5 years. Objectives The objectives of the study were to assess the level of knowledge, practice, and maternal-related factors influencing nutrition status among children under 5 years in Ibalikoma village Apac district. Methodology The study design was a descriptive cross-sectional study where data was collected using self-administered questionnaires given by 100 respondents using random sampling. Results Results showed that the majority 69(69%) knew that a child should be breastfed on demand. majority 85(85 %) knew that a child should spend at least 6 months on exclusive breastfeeding before initiating them on other feeds. About care taker’s practices, majority 56(56%) of the caregivers had stopped breastfeeding their children Conclusion The study established that the majority of the respondents had knowledge about exclusive breastfeeding and complementary feeding However most of the mothers did not put all the knowledge into practice due to lack of resources and citing unfavorable environments to apply what they knew. The nature of the work of caretakers, their level of education, and their economic status had a great influence on the applicability of the required nutrition practices. Recommendations There is a need for increased sensitization and awareness campaigns by the government of Uganda through the ministry of health specifically about the practical ways which suit the lifestyle in rural areas that can help improve the nutritional status among children under 5 in rural areas.